Analisis Faktor-Faktor yang Mempengaruhi Minat Wajib Pajak Orang Pribadi dalam Menggunakan E-Filling Sebagai Sarana Pelaporan SPT (Studi Empiris pada Wajib Pajak Orang Pribadi di KPP Pratama Malang Selatan) - Ardila Kurnia Susanti; Afifudin Afifudin; Umi Nandiroh (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This study aims to determine the factors that influence the intention to use e-Filling by individual taxpayers using the TAM modification approach. Sampling in this study using the slovin formula. This study uses primary data by distributing questionnaires directly to 98 individual taxpayers who are registered at KPP Pratama Malang Selatan. The analytical method used is path analysis with the help of SmartPLS 3. The results show that perceived usefulness and perceived ease of use  have a positive and significant effect on interest in using e-Filling.Keywords: Perceived usefulness, perceived ease of use, interest in using e-filling